The SBASE protein domain library, release 5.0: a collection of annotated protein sequence segments. - Fábián, P (1997)
SBASE 5.0 is the fifth release of SBASE, a collection of annotated protein domain sequences that represent various structural, functional, ligand-binding and topogenic segments of proteins. SBASE was designed to facilitate the detection of functional homologies and can be searched with standard database-search programs. The present release contains over 79863 entries provided with standardized names and is cross-referenced to all major sequence databases and sequence pattern collections. The information is assigned to individual domains rather than to entire protein sequences, thus SBASE contains substantially more cross-references and links than do the protein sequence databases. The entries are clustered into >16 000 groups in order to facilitate the detection of distant similarities. SBASE 5.0 is freely available by anonymous 'ftp' file transfer from <ftp.icgeb.trieste.it >. Automated searching of SBASE with BLAST can be carried out with the WWW-server <http://www.icgeb.trieste.it/sbase/ >. and with the electronic mail server <sbase@icgeb.trieste.it >which now also provides a graphic representation of the homologies. A related WWW-server <http://www.abc.hu/blast.html > and e-mail server <domain@hubi.abc.hu > predicts SBASE domain homologies on the basis of SWISS-PROT searches.